Genetic biomarkers in acute myeloid leukemia: will the promise of improving treatment outcomes be realized?. Issue 4 (August 2012) - Yang, Jay; Schiffer, Charles A
Recent progress in the molecular genetics of acute myeloid leukemia (AML) has shown this disease to be more heterogeneous than previously realized. Recurrent cytogenetic and mutational changes in leukemic blasts have been confirmed to have high prognostic significance. High-throughput techniques to analyze the AML genome in greater depth have revealed novel mutations with putative roles in leukemogenesis. The use of prognostic biomarkers has allowed for a more detailed categorization of AML based on risk. Despite this tremendous progress, the understanding of the mechanisms by which these changes influence leukemia growth and response to treatment is still limited, which in turn has hindered the development of rationally targeted therapies for AML. The integration of clinical, cytogenetic and molecular data will be essential to translate the current research momentum into better outcomes for patients with AML.